Extraction, Phytochemical Profiling, and Antibacterial Activity of n-Hexane Crude Extracts of Macroalgae Padina australis - Lenoera, Agnes; Panjaitan, Riong Seulina; Purwati, Purwati (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
Padina australis, brown macroalgae, has potential bioactive compounds that possess remarkable bioactivities including antimicrobial. The present study extracts macroalgae P. australis using Ultrasound assisted extraction (UAE) with n-hexane solvent, followed by screening phytochemical compounds. Moreover, the antimicrobial activity and MIC value of the n-hexane crude extracts of Padina australis was tested against Shigella sonnei, Escherichia coli, Salmonella typhi, and Bacillus cereus by using the disc diffusion method. This result demonstrates the optimum time of UAE process is at 10 minutes that yields 0.117 %. The phytochemical screening of n-hexane crude extracts of Padina australis macroalgae revealed the presence of secondary metabolites such as alkaloids, flavonoids, saponins, tannins, steroids and phenols. Antibacterial activity of this extract against Shigella sonnei, Escherichia coli, Salmonella typhi, and Bacillus cereus at 100 ppm concentration with inhibitory diameter range of 10.97 to 13.86 mm. Then, the n-hexane crude extracts of P. australis is potent against Bacillus cereus with MIC value of 6.25 ppm.